Tuning the properties of nickel nanoparticles inside SBA-15 mesopores for enhanced stability in methane reforming - Karam, Leila; Casale, Sandra; El Zakhem, Henri; El Hassan, Nissrine (Journal of CO2 utilization, 2017)
[Display omitted] •Calcination rate affects pore plugging and dispersion of nickel.•Optimum calcination rate enhances nickel stability in dry reforming of methane.•Coke is absent on confined particles of nickel inside the mesopores of SBA-15. The properties of nickel nanoparticles inside the mesopores of SBA-15 support were tuned by a careful control of the calcination rate. Ni/SBA-15 catalysts containing 5wt% nickel were prepared following three different calcination rate values (0.25 −0.5 −4.5°Cmin−1). Their properties were characterized by N2-sorption, X-ray diffraction (low and wide angles), temperature programed reduction and transmission electron microscopy. These catalysts were then tested in dry reforming of methane (DRM). As a result, the catalyst calcined at 0.5°Cmin−1 resulted in the formation of strong interaction between the active phase and the SBA-15 support, high nickel dispersion and accessibility that greatly enhanced its stability in dry reforming of methane.